2011
DOI: 10.1371/journal.pone.0020457
|View full text |Cite
|
Sign up to set email alerts
|

Myelin Basic Protein as a Novel Genetic Risk Factor in Rheumatoid Arthritis—A Genome-Wide Study Combined with Immunological Analyses

Abstract: Rheumatoid arthritis (RA) is a major cause of adult chronic inflammatory arthritis and a typical complex trait. Although several genetic determinants have been identified, they account for only a part of the genetic susceptibility. We conducted a genome-wide association study of RA in Japanese using 225,079 SNPs genotyped in 990 cases and 1,236 controls from two independent collections (658 cases and 934 controls in collection1; 332 cases and 302 controls in collection2), followed by replication studies in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…Previous studies using arrays spotted with cit-MBP peptides detected anti-cit-MBP-peptide antibodies in the experimental autoimmune encephalomyelitis (EAE) mouse model for MS but not in collagen-induced arthritis (CIA) mouse model (71). Here, we detected anti-cit-MBP antibodies in a large fraction of RA patients (ϳ80% of CCPϩ samples), which agrees with a previous report on the expression of MBP in the synovial lining and the presence of anti-cit-MBP in RA, although the prevalence of response has not been previously determined (64).…”
Section: Concept Of Contra Capturesupporting
confidence: 86%
See 1 more Smart Citation
“…Previous studies using arrays spotted with cit-MBP peptides detected anti-cit-MBP-peptide antibodies in the experimental autoimmune encephalomyelitis (EAE) mouse model for MS but not in collagen-induced arthritis (CIA) mouse model (71). Here, we detected anti-cit-MBP antibodies in a large fraction of RA patients (ϳ80% of CCPϩ samples), which agrees with a previous report on the expression of MBP in the synovial lining and the presence of anti-cit-MBP in RA, although the prevalence of response has not been previously determined (64).…”
Section: Concept Of Contra Capturesupporting
confidence: 86%
“…We used MBP as an example. We were particularly interested in mapping the epitope(s) for MBP, because it represented a poorly studied citrullinated antigen for RA and there was only one report of anti-cit-MBP in RA patients (64). Two isoforms of MBP were used for epitope mapping.…”
Section: Concept Of Contra Capturementioning
confidence: 99%
“…Environmental and genetic factors have been shown to be important for the onset of RA [1,2]. Anti-citrullinated peptide antibody (ACPA) and rheumatoid factor (RF) are autoantibodies frequently found in patients with RA [3e5].…”
Section: Introductionmentioning
confidence: 99%
“…African-American population has the highest risk for PCa, while Asians have the lowest 2. Recent technological developments have enabled us to perform genome-wide association study (GWAS) to detect associated genes or loci with diseases or quantitative trait in an unbiased approach 4. Previous genetic studies including GWAS have revealed more than 70 susceptibility genes to PCa 5.…”
Section: Introductionmentioning
confidence: 99%